Penyelesaian Sengketa Melalui Homologasi Dalam Penundaan Kewajiban Pembayaran Utang (PKPU): Studi Putusan Nomor 43/Pdt.Sus-PKPU/2020/PN Niaga Smg - Andrie Nindy Dwiantari; Sulthan Wahidy; Rizki Amar; Moh Saifa Abudillah (P3M dan Jurusan Syariah dan Ekonomi Bisnis Islam STAIN Sultan Abdurrahman Kepulauan Riau, 2026)
A Postponement of Debt Payment Obligations (PKPU) may be filed if the debtor is unable to continue paying their debts that are due and collectible; this may be filed by debtors with more than one creditor or by creditors. This study will discuss the legal considerations used by judges in ratifying settlement agreements and the legal consequences of homologation as in decision number 43/Pdt.Sus-PKPU/2020/PN Niaga Smg. This study is a descriptive literature study using a normative juridical approach. The findings of this study are, firstly, that the legal considerations used by judges in ratifying the settlement agreement are in accordance with Law No. 37 of 2004 concerning Bankruptcy and Suspension of Debt Payment Obligations (PKPU), namely that it complies with the provisions of Article 281(1) and does not contravene Article 285(2), so that the court is obliged to ratify the settlement agreement as stipulated in Article 285(1). Second, the legal effect of homologation is to bind all creditors as stipulated in Article 286. If the debtor fails to fulfil the terms of the settlement, the creditor may demand the cancellation of a settlement that has been ratified as stipulated in Article 170(1).